2018
DOI: 10.1093/cid/ciy213
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen as a Renoprotective Adjunctive Treatment in Patients With Severe and Moderately Severe Falciparum Malaria: A Randomized, Controlled, Open-Label Trial

Abstract: This randomized, controlled trial shows that acetaminophen reduces kidney dysfunction and risk of developing acute kidney injury, particularly in severe malaria patients who present with high plasma hemoglobin, supporting the hypothesis that acetaminophen inhibits cell-free hemoglobin-mediated renal tubular oxidative damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 29 publications
5
33
0
1
Order By: Relevance
“…Interestingly, a randomized control study in Bangladesh patients demonstrated that IV prostacyclin reduced the development of AKI [13,23]. Another randomized control trial found that acetaminophen greatly reduced serum creatine and lowered risk of AKI in patients with moderate to severe malaria [45]. As acetaminophen can be hepatotoxic, it must be used with caution as patients with malaria can experience liver dysfunction [46].…”
Section: Specific Therapiesmentioning
confidence: 99%
“…Interestingly, a randomized control study in Bangladesh patients demonstrated that IV prostacyclin reduced the development of AKI [13,23]. Another randomized control trial found that acetaminophen greatly reduced serum creatine and lowered risk of AKI in patients with moderate to severe malaria [45]. As acetaminophen can be hepatotoxic, it must be used with caution as patients with malaria can experience liver dysfunction [46].…”
Section: Specific Therapiesmentioning
confidence: 99%
“…Furosemide and mannitol are ineffective in preventing and treating AKI and BWF, respectively, and may be harmful [ 92 , 93 ]. On the basis of the ability of paracetamol to inhibit hemoprotein-mediated AKI [ 94 ], a recent RCT of paracetamol in Bangladeshi adults with severe malaria found that acetaminophen improved kidney function and reduced the development of AKI, particularly in patients with high cell-free hemoglobin levels at enrollment [ 95 ▪ , 96 ]. Larger studies of paracetamol in adults and children with malaria are currently ongoing to further assess this renoprotective effect.…”
Section: Treatmentmentioning
confidence: 99%
“…The following illustrates our suggested approach to assessing HTEs from RCT data and showing how this heterogeneity should be graphically visualised with the help of a multivariable risk model. We first constructed a multivariable risk model of death from severe malaria using data from more than 4000 patients from multiple randomised and observational studies (mostly Asian adults) [17,[21][22][23][24][25][26][27]. For all patients in this training dataset, risk of in-hospital mortality was then estimated using a mixed-effects logistic regression model, with the Fig.…”
Section: Case Study: the Hte Of Parenteral Artesunate For The Treatmementioning
confidence: 99%